Understanding Stunting Determinants in Urban Indonesia: Evidence from the Regional Technical Implementation Unit of Sekaran Public Health Center - Mukminin, Amirul; Sumanto, Reni Pawestuti Ambari; Wijayantiningrum, Tutuk (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
As of August 2023, a total of 39 stunting cases were recorded in the service area of Sekaran Public Health Center RTIU, covering five sub-districts. This study aims to analyze the risk factors contributing to the occurrence of stunting in the designated area.  Employing a qualitative descriptive design, the study gathered in-depth data through semi-structured interviews and field observations, involving eight purposively selected families with stunted children. Data collection was complemented by triangulation with community health workers and Posyandu cadres. Thematic analysis, following Braun and Clarke’s six-phase model, was used to identify emerging patterns and themes. The findings indicate that environmental conditions such as sanitation, toilet facilities, clean water sources, drainage systems, and housing floors were generally adequate. However, many mothers had a history of anemia and received only basic antenatal care, often from private providers. After childbirth, exclusive breastfeeding was rarely practiced, and children were frequently spoon-fed less than three times daily. This suboptimal nutritional intake was primarily due to the parents' work demands and the delegation of caregiving responsibilities to grandmothers or nannies. Additionally, the performance of the Integrated Health Service (Posyandu) in the area was limited to weighing and height measurement activities, without substantial educational or follow-up components. The results of this study imply that interventions to reduce stunting must extend beyond infrastructure and include behavioral changes in nutrition and caregiving practices. The limitation of this study lies in the small number of participants and its localized focus, which may not fully represent broader demographic variations. Future research is recommended to include larger and more diverse samples to enhance the generalizability of findings and explore the effectiveness of integrated, community-based interventions.